Correlation of Cord Lactate with Cord pH as a Morbidity Predictor in Term Neonates Delivered with Non-Reassuring Fetal Heart Status - Aluru Ananya; Kanta Kumari PML; B Vijayalakshmi; R Chandrasekhar; Naga Saritha Kolli (Asian Journal of Clinical Pediatrics and Neonatology, 2020)
Background: Perinatal asphyxia is accounting to 20% of neonatal mortalityin India. Cord lactate can be an alternative that is more readily available than cord pH and may help in early identification of birth asphyxia in resource limited settings. The aim of the current study is to correlate cord lactate levels with cord pH in term neonates with non-reassuring fetal heart status and thereby its use as a surrogate for cord pH. Subjects & Methods: Study design: Cross-sectional study. Setting: Neonatology unit at NRI general hospital, Chinakakani from August 2018 to July 2019. Study participants: All singleton term neonates delivered by assisted vaginal delivery or emergency caesarean section due to non-reassuring fetal heart status. Umbilical cord blood gas and lactate was obtained. Lactate was analysed by colorimetric method. Results: A total of 74 neonates were included. An analysis of cord pH & lactate, using correlation coefficient showed statistically significant p-values. Cord lactate was found to be statistically significant predictor for admission to NICU, post resuscitation care, invasive/noninvasive ventilation, and therapeutic hypothermia on multiple logistic regression analysis. Cord Lactate was found to have an Area under the curve (AUC) of 0.88 with no significant difference to cord pH on ROC curve analysis. Conclusion: Cord Lactate can be used as an objective test in predicting the neonates requiring NICU admission for morbidities related to fetal hypoxia similar to that of cord pH in term neonates.